(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
Today, digital technologies are penetrating all spheres of our lives. The widespread use of digital tools in the educational process also contributes to a significant increase in the quality of student learning. However, not only the provision of knowledge, but also the development of students’ creative abilities and independent thinking, that is, divergent thinking, is becoming an important social task. The concept of divergent thinking was introduced into scientific circulation by J. Guilford (1956), which expresses the creative and non-traditional direction of human thinking. According to Guilford, divergent thinking is a type of thinking aimed at finding not one, but several alternative solutions to a problem. In the works of N. Selwyn (2019), M. Prensky (2001), and D. Laurillard (2013) on the influence of the digital educational environment, it is noted that digital technologies have a positive impact on the formation of a student as a self-regulating, creative, and adaptable student. Scientists of Uzbekistan A. Tulaganov (2020)